Influência do estado nutricional e da composição corporal na evolução clínica dos pacientes com doença inflamatória intestinal - Back, Ivi Ribeiro [UNESP] (2014)
Introduction: Inflammatory Bowel Diseases (IBD) are diseases of unknown etiology and can develop an inflammatory response in the gastrointestinal mucosa of immune nature. Nutritional status is directly related to the severity of disease and its worsening may contribute to the negative prognosis and damage of the immune competence. The purpose of this study was to evaluate the nutritional status and body composition of IBD patients accompanied at the outpatient clinic of Inflammatory Bowel Disease of Clinical Hospital of Botucatu Medical School and identify nutritional predictors of clinical outcome in patients with Crohn's disease (CD) and Colitis ulcerative (UC). Methods: A cross-sectional was conducted study with clinical and nutritional evaluation of 141 patients followed at the Botucatu Medical School. We included pacients with confirmed diagnosis of CD or UC; adults, over eighteenyears old and of both sexes. Exclusion criteria was patients using nutritional supplements, pregnancy and lactating women and patients with chronic diseases. For the classification of the clinical activity of DC used the Crohn's Disease Activity Index (CDAI). To characterize the extent and evolutionary way DC used the classification of Montreal. The UC was classified according to the anatomical extent of the inflammatory process and assessment of disease activity, the Mayo score was used. Nutritional assessment the anthropometric measurements used were current weight, height, arm circumference (AC), triceps skinfold (TSF) and the thickness of the thumb adductor muscle (APM). Body Mass Index (BMI), arm muscle circumference (MAC) and corrected arm muscle area (CAMA) were also calculated. By bioelectrical impedance was calculated the Phase Angle and obtained Lean Body Mass percentage and Fat Mass percentage. Laboratory tests analyzed were: hematocrit, hemoglobin, total protein, albumin, C-reactive Protein and Erythrocyte Sedimentation Rate. The descriptive ...